(untitled) (Iranian Journal of Kidney Diseases, 2012)
Introduction. The ankle-brachial index (ABI), measurement of carotid artery intima-media thickness (CIMT), and assessment of the thickness of interventricular septum (IVS), are noninvasive methods used to predict subclinical atherosclerosis in hemodialysis patients. This study aimed to determine the prevalence of peripheral arterial disease and to assess the correlations between ABI, CIMT, the thickness of IVS, and blood parameters in hemodialysis patients. Materials and Methods. The ABI, CIMT, and the thickness of IVS were measured in 50 patients on hemodialysis. Data were collected regarding the levels of calcium, urine nitrogen, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride, cholesterol, creatinine, albumin in serum, as well as erythrocyte sedimentation rate. Results. Ten percent of the patients showed a reduced ABI (< 0.9). The mean values for ABI, CIMT, and IVS were 1.09 ± 0.13, 0.68 ± 0.11mm, and 9.83 ± 1.65 mm, respectively. The levels of calcium, cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglyceride in the serum of the patients with normal ABI were significantly higher than in patients with reduced ABI. There was a negative correlation between ABI and levels of serum LDLC (r = -0.29, P = .04) and triglyceride (r = -0.32, P = .02). Conclusions. The prevalence of peripheral arterial disease in the patients with CRF was 10% and it was correlated with several classical risk factors for atherosclerosis, including elevated LDL and cholesterol levels. CIMT and the thickness of IVS showed no apparent association with ABI.